Moisture stability enhancement of open-graded friction courses filling with oil shale waste based on interface linkage modification - Yingsong Li; Wei Guo; Xiaoming Huang; Zeqi Chen; Ziyue Zhou; Ying Gao (Materials & Design)
Oil shale waste (OSW), exhibits a high moisture absorption, which poses a potential moisture damage when filled in asphalt pavement. This study aims to enhance the moisture stability of Open-Graded Friction Courses (OGFC) filling with OSW based on the interface linkage of silane coupling agent (SCA). The moisture sensitivity test showed that the SCA effectively improved the moisture stability of OGFC filling with OSW. After linkage modification, its immersion Marshall stability and spring-thawing Marshall stability increased by about 36 % and 20 %, respectively. Dynamic shear rheometer test exhibited that SCA modified OSW asphalt mortar had the lowest complex modulus aging index of 1.12 %, which indicated that SCA inhibits the water intrusion. The consolidation of asphalt- SCA- OSW interface was 24.32 % higher than that of asphalt- OSW interface after 48 h immersion. After linkage modification, the adhesion rate between OSW and asphalt increased by 14.1 %, the surface energy of OSW decreased by 32.83 %, and the polar component decreased by 85.53 %. Molecular simulation experiments showed that the SCA could increase the adhesion energy between asphalt and OSW under wet condition by 34.5 %. The research findings can expand the application scenarios of OSW in pavement construction and diversify the methods for its utilization.